Urgent Percutaneous Coronary Artery Intervention and Coronary Artery Bypass Grafting in STEMI Patients with Confirmed COVID-19 - Keskin, Gokhan; Uysal, Ayhan; Erturk, Esra; Hafiz, Erhan; Dogan, Omer Faruk (Forum Multimedia Publishing, Llc, 2021)
Background: Our aim of this study was to evaluate the cardiac symptoms, coronary angiographic results, and clinical outcomes of patients with confirmed COVID-19 and ST-segment elevation with myocardial infarction (STEMI) or myocardial ischemia. Material and methods: Thirty-seven patients, who already were confirmed with COVID-19 using reverse transcriptase-polymerase chain reaction (RT-PCR), were admitted to our hospital due to chest pain with STEMI. The median patient age was 66 years (range: 27-84 years). Female/male ratio was 22/15. We performed a second RT-PCR test in all patients. We investigated myocardial enzymes (creatine kinase myocardial band (CK-MB), cardiac troponin-I (c-TnI), and C-reactive protein (CRP), and liver enzymes (alanine amino transferase (ALT) and aspartate amino transferase (AST) also were measured. Blood d-dimer, thromboplastin time (PT), partial thromboplastin time (PTT), and fibrinogen were investigated. Transcutaneous oxygen saturation was monitored for each patient in the emergency department (ED). To evaluate myocardial wall abnormalities, transthoracic echocardiography was performed. Results: Coronary artery disorders requiring revascularization were detected in 25 patients (67.5%). There was no evidence of coronary artery disease in the remaining 12 patients. Out of 25, nine coronary artery disease patients had a history of coronary intervention (24.3%). All patients had high levels of myocardial enzyme release. Percutaneous coronary interventions (PCI) were performed in patients with culprit lesion(s). Success rate of PCI was 87.5% (N = 21). The median number of stent use was 2.9 +/- 0.7 (range: 1-4). Because PCI failed in four patients, we suggested elective coronary artery bypass grafting (CABG) surgery after medical treatment. Six patients required re-intervention owing to early stent thrombosis (30%). Seven patients died after PCI (33.3%). For patients with negative or positive RT-PCR test results, we performed thoracic computed tomography (CT), which is a sensitive diagnostic method for COVID-19. Interlobular septa! and pleural thickening with patchy bronchiectasis in the bilateral or unilaterally lower and/or middle lobe(s) were the main pathologies in 24 patients. D-dimer, fibrinogen, and CRP levels were high in 11 PCI patients with bilaterally pulmonary involvement by COVID-19 (52.3%), while fibrin degradation products did not significantly change. For three patients with normal coronary arteries with a transient hypokinesia or hypokinesia as result of myocarditis, we decided to perform atypical Takotsubo cardiomyopathy. We medically treated using inodilator (levosimendan), diuretic, angiotensin-converting enzyme inhibitors and beta-blockers. To prevent the risk of thromboembolism, we also administered a heparin drip. The myocardial contractility of the apex did improve, and patients were discharged from the hospital, with the exception of one young female patient. She is following in the ICU with stabil hemodynamics. Conclusion: Chest pain with STEMI can develop in patients with confirmed COVID-19. Nearly one-third of patients had COVID-19 with chest pain and concomitant STEMI and normal coronary angiography (32.4%). Urgent PCI may be performed in hemodynamically unstable patients with high mortality. Complications, including sudden cardiac arrest, severe ventricular arrhythmia, and Takotsubo cardiomyopathy, related to COVID-19 patients with normal coronary arteries.